(untitled) (Texas Journal of Multidisciplinary Studies, 2025)
This article analyzes and studies portrait articles dedicated to the great Uzbek poet and great thinker Alisher Navoi, the Hero of Uzbekistan, People’s Poet of Uzbekistan Abdulla Oripov